JESSICA WONGSO AND THE SEARCH FOR HIDDEN CAUSALITY IN THE POISONED COFFEE CASE - Kanzi Fathan (Jurnal Impresi Indonesia, 2024)
The 2016 murder case of Wayan Mirna Salihin in a Jakarta cafe sent shockwaves across Indonesia. Mirna tragically passed away after consuming coffee suspected of being laced with cyanide. Jessica Wongso, her friend, received a life sentence for the crime. The case garnered widespread attention due to the cyanide's involvement, the intricate relationship between Jessica and Mirna, and the contentious trial proceedings. Public outcry and debates over the evidence's reliability sparked inquiries into potential hidden motives. This study delves into uncovering these concealed factors, employing qualitative methodologies and analyzing psychological, social, cultural, and environmental aspects. By doing so, it aims to shed light on Jessica's motivations and the context surrounding her actions, thereby contributing to public comprehension and legal discourse. Despite Jessica's conviction, doubts persist, particularly regarding her motives and the chain of causality. Police investigations relied on coffee orders and Jessica's cyanide purchase, yet inconsistencies in DNA testing and unclear motives fueled skepticism. Exploring causality helps discern cause-and-effect relationships, identify underlying issues, assess evidence, prompt further investigations, and unveil concealed truths. Beyond Jessica's culpability, questions linger regarding cyanide's broader implications, potential third-party involvement, Jessica's psychological profile, and the clarity of causality. This case underscores the intricacies of real-life causality, emphasizing the importance of a nuanced understanding in ensuring justice prevails.